2022
DOI: 10.3390/ma15176072
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Behavior of Aluminum Matrix Nano-Composite Automobile Disc Brake Rotor Using Finite Element Method

Abstract: Analysis of mechanical and thermal behaviors during braking has become an increasingly important issue in many transport sectors for different modes of transportation. Brake failure generated during braking is a complex phenomenon confronting automobile manufacturers and designers. During braking, kinetic energy is transferred to thermal energy, resulting in the intense heating of disc brake rotors that increases proportionally with vehicle speed, mass, and braking frequency. It is essential to look into and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The grid aspect ratio was close to 1, and the analysis of the grid aspect ratio indicated that the drawn transformer winding grid was of good quality. 41 To determine the AC impedance, the magnetomotive force was simulated by Ansys Electronics Desktop. A structure with a small impedance was selected for the design.…”
Section: Simulationmentioning
confidence: 99%
“…The grid aspect ratio was close to 1, and the analysis of the grid aspect ratio indicated that the drawn transformer winding grid was of good quality. 41 To determine the AC impedance, the magnetomotive force was simulated by Ansys Electronics Desktop. A structure with a small impedance was selected for the design.…”
Section: Simulationmentioning
confidence: 99%